PERANCANGAN APLIKASI PEMBELAJARAN BAHASA ASING YANG INTERAKTIF MENGGUNAKAN METODE MERN - Faris Mas’ud; Nuryuliani Nuryuliani (Asosiasi Dosen Muda Indonesia, 2024)
There are many ways to learn some foreign language. Some people are afraid to learn a foreign language because they are afraid of the high costs. This can be solved by using a website-based online chat application, which provides features for practicing foreign language conversations. The